Reduced Levels and Disrupted Biosynthesis Pathways of Plasma Free Fatty Acids in First-Episode Antipsychotic-Naïve Schizophrenia Patients - Zhou, Xiang; Long, Tao; Haas, Gretchen L.; Cai, HuaLin; Yao, Jeffrey K. (Frontiers in Neuroscience, 2020)
Membrane phospholipid deficits have been well-documented in schizophrenia (SZ) patients. Free fatty acids (FFAs) partially come from the hydrolysis of membrane phospholipids and serve as the circulating pool of body fatty acids. These FFAs are involved in many important biochemical reactions such as membrane regeneration, oxidation, and prostaglandin production which may have important implications in SZ pathology. Thus, we compared plasma FFA levels and profiles among healthy controls (HCs), affective psychosis (AP) patients, and first-episode antipsychotic-naïve schizophrenia (FEANS) patients. A significant reduction of total FFAs levels was observed in SZ patients. Specifically, significant reductions of 16:0, 18:2n6c, and 20:4n6 levels were detected in FEANS patients but not in APs when compared with levels in HCs. Also, disrupted metabolism of fatty acids especially in saturated and n-6 fatty acid families were observed by comparing correlations between precursor and product fatty acid levels within each fatty acid family. These findings may suggest an increased demand of membrane regeneration, a homeostatic imbalance of fatty acid biosynthesis pathway and a potential indication of increased beta oxidation. Collectively, these findings could help us better understand the lipid metabolism with regard to SZ pathophysiology.